Marxist Aesthetics: A Historical Antinomy - Bolt, Mikkel (The Nordic Journal of Aesthetics, 2025)
This essay discusses the current status and meaning of Marxist aesthetics. As a somewhat heavy-handed gesture, some might say breast-beating, it attempts to link Marxist aesthetics to the question of revolutionary politics. To achieve this, it examines the relationship between revolutionary strategy and imagination in a previous era discussing a short paragraph in Lenin’s What is to be Done?, in which Lenin refers to Dmitry Pisarev. By comparing Lenin and Pisarev, the essay highlights two contrasting approaches within revolutionary Marxism, characterised by two divergent conceptions of art. Nevertheless, both sought to relate art to revolutionary politics. The essay ends by asking whether this is possible today, and, if not what this means for the project of Marxist aesthetics – does it even exist?